Compensation systems in sustainable land management. Potentials and challenges exemplified by the Rendsburg region - Goede, Paul (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Despite all efforts to date, the original 2020 targets for reducing land use have not been met. In growing urban regions, the most urgent challenge at present seems to be to moderate increasing conflicts over the use of land, a resource that is becoming increasingly scarce. For sustainable land management in times of surging interdependencies across municipal boundaries, inter-municipal cooperation is becoming increasingly important. However, competitive incentives make sustainable, cooperative settlement development more difficult. In this context, compensation systems that enable a systematic balance of interests and provide incentives for sustainable, land-saving settlement development, are currently being discussed. Ideally, they should resolve the contradictions between local interests and regional goals, if they are properly adapted to the respective region. This paper places compensation systems in the international debate and proposes a categorization for further analysis. Using the example of the Rendsburg region (Germany), success factors for compensation systems in land management are discussed.
Keywords: Inter-municipal cooperation; Compensation systems; Land management; Sustainable settlement development; Rendsburg (Germany)